Morpho-biochemical characterization and D2 analysis of watermelon (Citrullus lanatus) landraces from India and exotic germplasm - SINGH, DILBAG; SINGH, RAJINDER; SAINI, JOHAR SINGH; SINGH, PARVEEN KUMAR (The Indian Journal of Agricultural Sciences, 2018)
Eighty eight watermelon (Citrullus spp) genotypes representing Indian landraces and exotic accessions of diverse geography were characterized for 17 plant, fruit, seed and quality traits during 2015 and 2016. The germplasm evaluated showed significant differences for all the agro-morphological and fruit quality characters. Cluster analysis using Mahalanobis (D2) assigned genotypes into 10 distinct clusters. Clusters I and II containing landraces collected from Uttar Pradesh and Rajasthan province of India showed least inter cluster distance depicting them to be morphologically close to each other. Other clusters were a mixture of accessions grouped together irrespective of their origin. Cluster × and Cluster III were most divergent. Genotypes of Cluster III were best for earliness in flowering and fruit maturity, Cluster V members best for TSS, lycopene and total carotenoids, whereas Cluster VIII constituted genotypes having largest fruit size and yield/plant. Indigenous landraces excelled in earliness, fruit number, dry matter and lowest 100 seed weight. Exotic germplasm was best for yield and fruit quality parameters. Breeding strategies involving indigenous landraces would serve to broaden the genetic base, crop improvement as well as their conservation.